Effects of victim’s body posture and attacker’s gender on slashing attacks: a biomechanical study - Li, Shangxiao; Yuan, Shufang; Shi, Yi; Ni, Bin; Guo, Wenxia; Yang, Chaopeng; Wang, Mingzhi; Hao, Weiya (Frontiers in Bioengineering and Biotechnology, 2024)
Objective Sharp force injury has been and will remain to be a major cause of violent death; however, scientific evaluations on the impact of body posture of the victim and gender of the perpetrator on sharp force injury have been scarce. The purpose of this study was to evaluate the biomechanical characteristics found in individuals (male and female) when using a Chinese kitchen knife to slash the neck of a dummy while it was in the standing and supine positions. This work offers a solid basis for forensic identifications, criminal investigations, and court trials. Methods A total of 12 male and 12 female college students participated in this study. Kinematic, kinetic, and surface electromyography (sEMG) data were evaluated when slashing the neck of a dummy while it was in the standing and supine positions using a Chinese kitchen knife. Results When slashing the neck of a standing dummy, participants showed shorter contact time (19.5%) and slower shoulder velocities (30.9%) as well as higher hip velocity (26.0%) and increased root mean square (RMS) and integral electromyography (iEMG) for the anterior deltoid (51.3% and 51.2%, respectively) compared to those while the dummy was in the supine position (all p < 0.05), regardless of gender. When slashing a dummy’s neck while it was in standing and supine positions, male participants showed higher shoulder, elbow, and wrist velocities (22.6%, 22.7%, and 24.4%, respectively) and higher slashing velocity (19.8%), slashing force (24.2%), and energy (46.2%) than female participants (all p < 0.05). In addition, male participants showed shorter contact time (17.8%), and the values of RMS and iEMG of the anterior deltoid, biceps brachii, extensor carpi radialis longus, and flexor carpi ulnaris were less than those of female participants (98.9%, 47.3%, 65.6%, and 33.4% for RMS and 115.1%, 59.4%, 80.1%, and 47.8% for iEMG, respectively). Conclusion There was no difference in slashing speed, slashing force, and energy when using a Chinese kitchen knife to slash the dummy’s neck while it was in different body postures (standing and supine), suggesting a similar level of injury severity. However, there were significant differences in slashing action patterns between the two body postures, with longer contact time, smaller hip velocity, greater shoulder velocity, and less muscle activation level of the deltoid exertion when slashing the dummy’s neck in the supine position. Gender may have a greater effect on the severity of slashing, and the gender difference may be partly related to the body weight difference. The findings from this study may provide quantitative indicators and references for analyzing the motive behind the crime, as well as for case reconstruction, and for the court’s conviction and sentencing processes.